Pengaruh Pemberian POC Limbah Buah dan Kotoran Ayam Terhadap Pertumbuhan dan Produksi Kacang Panjang (Vigna sinensis L.) - Ansyari, Khairul; Siregar, Maimunah; Sembiring, Desi Sri Pasca Sari (JURNAL AGROPLASMA, 2025)
Fertilization using organic fertilizers in agricultural land can increase the number of organisms in the soil and the chemical, physical and biological properties of the soil can be improved. This study aims to determine the effect of providing POC fruit waste and chicken manure on the growth and production of long beans (Vigna sinensis L.) and to determine the best dose for the growth and production of long beans. This study applies a Factorial Randomized Block Design with 2 treatment factors repeated 3 times. Factor one concentration of POC fruit waste consists of 4 levels: P0 = 0 ml / L / plot, P1 = 200 ml / L / plot, P2 = 300 ml / L / plot and P3 = 400 ml / L / plot. Factor 2 dose of chicken manure fertilizer consists of 4 levels: K0 = 0 kg / plot, K1 = 2 kg / plot, K2 = 4 kg / plot and K3 = 6 kg / plot. The parameters observed included plant length, stem diameter, number of pods per sample/harvest, pod length/sample, pod weight per sample and pod weight per plot. The results of this study indicate that the provision of POC concentration of fruit waste and chicken manure fertilizer doses have a significant effect on all observed variables. There was no interaction between the provision of POC concentration of fruit waste and chicken manure fertilizer doses on all growth and production variables of long beans (Vigna sinensis L.) Keywords: fruit waste, chicken manure, long beans